Analysis of Teachers’ Variation Skills in Teaching at Elementary School - Yosa Widya Casetama; Ratnasari Diah Utami (STAI Hubbulwathan Duri, 2023)
This study aimed to determine the skills of teachers in applying learning variations. This study used qualitative descriptive research designs conducted at a public elementary school in Surakarta, Indonesia. The subjects in this study were class II, III, IV, and V teachers using a purposive sampling technique to select the research sample. The data were collected through observation, interview and documentation techniques. Validity in this study used source triangulation and engineering triangulation. Analysis techniques used by the researchers was interactive models in the form of data reduction, data presentation and drawing conclusions. The results in the study concluded that teachers have done a fairly good variety of learning. Variations of teachers in learning are like using ice breaking in lessons, using question and answer methods and discussions. In this study it was found that the variety of learning media used by teachers included using picture books, using character cards in learning, and using LCDs and laptops as learning media. The variety of interactions used by the teacher is to use a clear, loud voice, and the interactions are carried out properly, as well as eye contact between the teacher and students. The obstacles faced by teachers are the lack of ice breaker mastered by the teacher, difficulties in focusing students' attention, and errors still often occur from the media used such as laptops and LCDs. The conclusion in this study is that the teacher has implemented several variations in learning quite well, but there are still obstacles in its application.